A bio-hybrid material for adsorption and degradation of phenanthrene: bacteria immobilized on sawdust coated with a silica layer. Issue 109 (9th November 2016) - Li, Jinghua; Guo, Chuling; Liao, Changjun; Zhang, Menglu; Liang, Xujun; Lu, Guining; Yang, Chen; Dang, Zhi
Abstract : Membrane permeability of bacteria immobilized in silica-coated sawdust was increased, and its metabolic activity toward Phe was enhanced. Abstract : Cell immobilization technology has been considered as an effective method for bioremediation of hydrocarbon-contaminated soil. However, bacteria immobilized by a single method often encounter some problems, e.g., cell leakage, cellular damage and no reproduction. In this study, a biomimetic hybrid material was constructed by pre-immobilization of bacteria on sawdust followed by coating a silica layer through vapor deposition (Silica-IC). The viability and metabolic activity of Silica-IC were investigated. Results showed that the silica layer covering the bacterial agent could significantly reduce cell leakage from sawdust without losing reproductive capacity on nutrient plates. A viability assay by SYTO9/PI in flow cytometry indicated that the proportion of live cells was decreased 30% and injured cells was increased 23.9%, while that of dead cells was still below 2.5% during storage at 4 °C for 15 days, i.e., membrane permeability of Silica-IC was increased, indicating bacterial cells in Silica-IC were able to maintain long-term storage stability and shelf life. The metabolic activity of Silica-IC toward phenanthrene (Phe) was enhanced both in liquid and soil. Phe degradation kinetics of Silica-IC in liquid medium well fitted an adsorption–degradation model, suggesting that the silica layer did not inhibit Phe diffusion. Moreover, the Phe removal percentage of Silica-IC in soil was up to 93.4% on day 2. Silica-IC in soil grew well and the growth was closely related to the residual amount of Phe. This work provides a route to develop a wide range of bio-materials for bioremediation.